Mountains of water [videorecording] the terraces and traditions of the Ifugao - Corre, Fruto
The Ifugao people came from Cordillera mountains of Northern Philippines. Through thousands of years, they designed, built and maintained the Ifugao rice terraces. These are one of the living wonders of the world, a World Heritage Site. Like giant shimmering steps stretching out as far as eyes can see, these ponfields of the Ifugao have been called the greatest agricultural achievement in human history. This skin water and stone blankets the steep mountains slopes of the Cordillera to hights five thousand feet. If palce end to end, it is estimated that this would reach halfway around the world. In terms of engineering and sheer scale, there are no other terraced rice cultivation areas in the world that can compare with the Ifugao Terraces.